Maternal and Perinatal Complications inTriplet Pregnancies in Retrospective Study - Hassan , Nessrean Ahmed; Al Sereah, Ghugran (Diyala Journal of Medicine, 2019)
Background: A retrospective study of maternal and neonatal complication of triplet pregnancies in Basrah Maternity and Child Hospital and in Kammal Al-Samarayei Hospital for period of 2011-2012. Aim: Assess frequency of obstetrical and perinatal complication and factors affecting outcome Methodology: We reviewed the obstetrical files , the data collected included maternal age , parity, fetal weight , mode of delivery and mode of conception from peroid the 1st of June 2011 to 31st of June 2012. Result: The rate of triplet increase with increasing of maternal age (30-39) and in primigraivda due to ovulation induction also increase rate of C. S, PE, PROM, Anemia, PPH, preterm delivery were (88.89%,19.4%, 30.5, 55.55%,11.11%,83.33%) respectively. The higher rate of deliveries occurred between 32-34 weeks and birth weight between 1550-2000 gm (36.36%, 39.81%) respectively. increases rates of abortion 18.1%. Conclusion: There were increasing rate of complication both maternal and fetal with triplets prematurity, still birth congenital abnormality, and C.S.